(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
The recently implemented curriculum for secondary History in South African schools - as set out in the Curriculum and Assessment Policy Statements (CAPS, 2011) - presents no explicit statement of the view of history informing its construction. While it is clear that the development of historical skills is intrinsic to the stated intention of CAPS, this gap is problematic. This is because it leaves assumptions about the nature of history unaddressed. At the same time, historiography is difficult. This article asks whether, in tackling three CAPS sections of Ghanaian history - through the history of cocoa - learners could be introduced to historiography in a productive manner. It provides a sample narrative of Ghana’s cocoa industry from the late 19th century onwards. It shows how the topic lends itself to an historiographical exploration which may be used to initiate learners into constructing their own narratives and in so doing, into engagement with historiographical issues.